Play and Imagination in Developing Language Teacher Identity-in-Activity - Paula Golombek; Patrick Klager (Ilha do Desterro)
Teacher identity and practice have been characterized as being inextricably linked, highlighting the need for L2 teacher educators to support the development of novice teacher identity and the practices that align with it. Informed by a sociocultural perspective on teacher learning (Johnson, 2009), this study traces the development of the identity of a novice teacher as he grapples with a tension while teaching an advanced grammar class. By conducting a narrative inquiry (Johnson & Golombek, 2002), he identiied a contradiction between his identity-in-activity (Cross, 2006), expressed through the image of the ‘grammar inquisitor’ teaching to the test and the communication-focused instructor he aspired to be. His narrative inquiry created a mediational space in which he could ‘play’ with images, as well as academic concepts that had been introduced in a graduate course on genrebased instruction, and ‘imagine’ a more satisfying identity-in-activity, expressed as ‘synergy’ in a curriculum unit he designed for his grammar class.